ACCELERATION AND STRENGTHENING OF SHARIA FINANCIAL INCLUSION THROUGH MERGING SHARIA BANKING IN INDONESIA - Syarifuddin, Syarifuddin; Rusanti, Ega; Octaviany, Mega; Mansyur, Abdurrahman (Universitas Airlangga, 2021)
Islamic banking in Indonesia is slowly experiencing significant developments both in terms of number of assets and its financial performance. On the other hand, the market share was only able to grow by 6.18 percent with grow rate less than 5 percent. Therefore, one of the strategies to increase and accelerate the growth of Islamic banking is through a merger. The purpose of this study is to provide an overview of the potential development of Islamic banking after the merger as an effort to strengthen the inclusion and acceleration of Islamic finance in Indonesia. The method used is in the form of a systematic analysis review by collecting various secondary data and then conducting a quality assessment to obtain in-depth research objectives. The results found through content analysis indicate that the merger strategy provided added value to the banking industry through greater market expansion, increased cost efficiency, financial performance, and lowering prices, to meet the public need for sharia-based financial services. Through a merger strategy, Islamic banking is able to become a new pillar of national economic strength and encourage Indonesia to become the center of the world on Islamic finance.